Two new species of Phyllanthus (Phyllanthaceae) endemic to the Brazilian Atlantic Rainforest - Torres, Alicia Marques; Silva, Marcos José Da; de Sá Cordeiro, Wesley Patrício Freire; Athiê-Souza, Sarah Maria; Sales, Margareth Ferreira De (Phytotaxa, 2020)
Two new species, Phyllanthus itamarajuensis and P. tuberculatus (Phyllanthaceae), currently restricted to the Atlantic Forest of Bahia State, Brazil, are described and illustrated. Phyllanthus itamarajuensis is distinguished by having long styles (2–2.2 mm long) associated with subshrubby habit, discretely asymmetrical basal leaves, and anthers with vertical dehiscence. Phyllanthus tuberculatus is characterized by glabrous leaves, a long pistillate pedicel (18–20 mm long), flowers of both sexes 5-merous, disk of the staminate flowers with five obtriangular segments with tuberculated surfaces, each being separated by a deep recess, and each with a central pore, anthers with non-divergent thecae, and a patelliform pistillate disk. The systematic position of both new species is discussed, and comments are provided on their morphological relationships, geographic distribution, conservation status, environmental preferences, and phenology.